Student pathways to understanding the global virtual teams: an ethnographic study. Issue 1 (2nd January 2019) - Dai, Yun; Lu, Stephen; Liu, Ang
ABSTRACT: Based on a two-year ethnographic study of global virtual teams (GVTs) ( n  = 323) in a technology-enhanced global course among six universities (i.e. U.S., China, South Korea, Germany, Israel, and India), this paper presents how and in what ways the participating students made sense of and constructed understandings about the interactive learning environment. Focusing on the student engagement, this study identified three pathways in which they negotiated and developed their respective understandings about technology, culture, and teamwork in GVTs. In each pathway, it was found that students engaged in the development process of reflecting upon problematic experiences, revolving unanticipated challenges, and establishing new ways of being, doing, and thinking. This study highlights the dynamic nature of understanding construction and provides important implications about how to implement GVTs and support students to succeed in GVTs.